Longitudinal associations of callous-unemotional and oppositional defiant behaviors over a three-year interval for Spanish children. (May 2020) - Servera, Mateu; Seijas, Raquel; García-Banda, Gloria; Barry, Christopher T.; Beauchaine, Theodore P.; Burns, G. Leonard
Abstract: The objective was to determine the longitudinal associations between callous-unemotional (CU) and oppositional defiant (OD) behaviors from the first to fourth grades for Spanish children. Four possible outcomes were evaluated: (a) CU behaviors in the first grade predict increases in OD behaviors in the fourth grade, controlling for OD behaviors in the first grade; (b) OD behaviors in the first grade predict increases in CU behaviors in the fourth grade, controlling for CU behaviors in the first grade; (c) both unique effects are significant; and (d) neither unique effect is significant. A longitudinal panel model with two latent variables (CU and OD behaviors), three sources (mothers, fathers, teachers), and two occasions (spring of the first and fourth grades) was used to evaluate the four possibilities among 758 (54% boys) first grade and 469 (53% boys) fourth grade Spanish children. For mother-, father-, and teacher-reports, OD behaviors in the first grade predicted increases in CU behaviors in the fourth grade, after controlling for CU behaviors in the first grade, whereas CU behaviors in the first grade did not predict increases in OD behaviors in the fourth grade, after controlling for OD behaviors in the first grade. OD behaviors thus conferred independent vulnerability to increases in CU behaviors 3 years later among young children.